PENGARUH BASIS BEESWAX DAN PARAFFIN WAX TERHADAP SIFAT DAN STABILITAS FISIK SEDIAAN LIPSTIK EKSTRAK ETANOLIK BUNGA KEMBANG SEPATU (Hibiscus rosa-sinensis L.) BESERTA UJI IRITASI PRIMERNYA - , RR. OCTAVIANI K. P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lipstick quality can be affected by the dye and base composition. Natural dyes areoften used empirically is anthocyanins contained in the flower of hibiscus (Hibiscus rosa-sinensis L.). The use of various types and compositions of different wax bases can provide different characteristics in lipstick. This study aims to determines the effect of a combination of beeswax and paraffin wax in various formula of lipstick from hibiscus flower extract in the physical properties, physical stability, and security. Anthocyanin dyes obtained from hibiscus flower in maceration with 96% ethanol. Lipstick made in 3 formulas consisting of formula 1 (10% Beeswax and 15% Paraffin wax), formula 2 (14% Beeswax and 11% Paraffin wax),and formula 3 (18% Beeswax and 7% Paraffin wax) with 6% of hibiscus flower extract. Lipstick tested physical properties and stability (organoleptic, hardness, adhesion, and melting point) for 4 weeks after the making. Security level of lipstick, tested with primary irritation test using female albino rabbits. Data were tested by One-Way ANOVA with confidence level 95%, followed by Tukey test. Organoleptic data were analyzed descriptively. The result showed that hibiscus lipstick produces a purple color, characteristic odor, and tasteless when applied topically. Lipstick on formula 1 and 3 are stable in storage in all response (organoleptic, hardness, adhesion, and melting point), while formula 2 is unstable in response to adhesion. Lipstick with ethanol extract of hibiscus flower (Hibiscus rosa-sinensis L.) as natural dyes do not provide primary irritation reactions (erythema dan edema) in test animals.